Gross, histological and electron microscopical features of the hard palate mucosa in the one-humped camel (Camelus dromedarius) - Attia A. Moselhy; Hanaa M. El-Ghazali (Iraqi Journal of Veterinary Sciences, 2023)
The purpose of the current work is to study mucosa of the camel hard palate morphology by gross anatomy, morphometric analysis in addition to light and scanning electron microscopy (SEM). Ten heads of freshly slaughtered camels were collected from Zagazig abattoir. The selected camels were in good general condition, their ages were ranged around three to five years. Anatomically, the hard palate was elongated and it could be divided into a narrow rostral part and a caudal wide part with about 13-14 transverse palatine ridges. The dental pad was a crescentic thick plate at the rostral end of hard palate. The incisive papilla is triangular prominence situated behind the dental pad in the median plane and is surrounded by shallow groove, microscopically, the mucosa of hard palate consisted of a keratinized squamous epithelium. The submucosa comprised from vascularized collagenous connective tissues run in various directions. The soft caudal part of the hard palate is distinguished by lobulated serous acini and it was rich in adipocytes. Scanning electron microscopy demonstrated the stratification of the epithelium; with excessive desquamation and sloughing of the epithelial cells. By high magnification, the microplicae system was inform of irregular surface separated by septae.